Developing Community Public Health Interventions by Pharmacy Students during the SARS-COV2 Pandemic in Costa Rica - Carrillo Ramírez, Valeria (2022)
Objective: To describe the development of virtual community interventions within the framework of public health interventions in community pharmacies, as a didactic strategy in university education from a constructivist approach for its subsequent implementation at times when these initiatives cannot be carried out face to face. Method: The students developed virtual interventions in communities or specific population groups on the topics of vaccination, asthma, depression, and fibromyalgia, previously chosen by the professors. The interventions were developed in accord with the 10 essential services in public health and with the mandatory participation of the community or interested stakeholders; interventions consisted of six phases: description of the community, problem identification, proposal of an action plan, construction of the interventions, marketing plan development, and the evaluation of interventions. To identify the problem, students conducted interviews on people familiar with each assigned topic, to identify common needs or concerns. These common needs or concerns were considered the aspects on which the participating population agreed were considered as the problem to work on. Results: The interventions developed were mainly talks, workshops, and virtual educational campaigns through infographics, posters, and social networks. Conclusions: The activities of the course were easily adapted to the virtuality, which could mean a reconsideration of the course modality. The use of virtuality for the development of health interventions in the community is an important resource that facilitates access to health education for the population especially for those who live in rural or remote areas. It constitutes a way of providing people with digital tools for self-care in health.